2023
DOI: 10.1371/journal.pone.0294601
|View full text |Cite
|
Sign up to set email alerts
|

Associations of production characteristics with the on-farm presence of Fasciola hepatica in dairy cows vary across production levels and indicate differences between breeds

Andreas W. Oehm,
Yury Zablotski,
Martina Hoedemaker
et al.

Abstract: Fasciola hepatica is one of the economically most important endoparasites in cattle production. The aim of the present work was to evaluate the relevance of production level on the associations of on-farm presence of F. hepatica with farm-level milk yield, milk fat, and milk protein in Holstein cows, a specialised dairy breed, and in Simmental cows, a dual purpose breed. Furthermore, we investigated whether differential associations were present depending on breed. Data from 560 dairy farms across Germany hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…Productive losses in ruminants caused by fasciolosis include the condemnation of bovine livers, cost of treating the disease, and reduction of fertility and milk production ( Howell et al, 2015 ; Oehm et al, 2023 ), in addition to death in acute cases and outbreaks ( Adrien et al, 2013 ). Regarding weight gain, Costa et al (2019) carried out a study in 2016 in Uruguay and confirmed loss of carcass quality in infected cattle, with the most notable weight differences being in the younger age groups.…”
Section: Pathology and Production Impactmentioning
confidence: 99%
“…Productive losses in ruminants caused by fasciolosis include the condemnation of bovine livers, cost of treating the disease, and reduction of fertility and milk production ( Howell et al, 2015 ; Oehm et al, 2023 ), in addition to death in acute cases and outbreaks ( Adrien et al, 2013 ). Regarding weight gain, Costa et al (2019) carried out a study in 2016 in Uruguay and confirmed loss of carcass quality in infected cattle, with the most notable weight differences being in the younger age groups.…”
Section: Pathology and Production Impactmentioning
confidence: 99%